Analisis Pengelolaan Dana Desa Dalam Meningkatkan Kesejahteraan Masyarakat Pada Desa Suko Kecamatan Sidoarjo - Muhammad Thomi Irvianto; Ketut Bayagkara (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to describe the Analysis of Village Fund Management in Improving Community Welfare in Suko Village, Sidoarjo District. The focus of this research is: 1) Village Fund Management Plan 2) APBD Accountability Steps 3) Community Welfare. The approach in this research is qualitative research, while the research object is in Suko Village. The subjects of this study are: 1) Village Fund planning activities 2) APBDes data for 2022 3) Village officials & village communities. The method used in this research is descriptive method. Data collection techniques are observation sheets, interview guidelines and documentation. Data management is carried out using a qualitative descriptive analysis. The results of the study show that the management of village funds has increased and been completed both by the village government and by the community.